Harm Reduction in the reality of the CAPS-ad in Quixadá (CE) - Sobral de Lima, Leandro (Argumentum, 2020)
This text presents a discussion based on research from the Conclusion Work for Integrated Residency in Health, with emphasis on mental health, and its main objective is to analyse the level of understanding of the multi-professional team of the CAPS-ad in Quixadá (CE) regarding the harm reduction policy and its relationship to actions developed in the institution's daily life. Qualitative research was carried out and the tools used in the collection and analysis of the data were: participant observation with recording in field diaries; semi-structured interviews; bibliographic research and content analysis. As the main results, from the speech of the interlocutors and in healthcare practices, we identified the existence of a critical understanding of drugs policy in Brazil and only a superficial knowledge regarding the harm reduction strategy. We also noted the daily challenge to, “put into practice”, forms of healthcare in line with the harm reduction strategy, in addition to the socialisation of information.